Georges Clemenceau France - Watson, David Robin (Haus histories, 2008)
For many, the role of Georges Clemenceau is still based on John Maynard Keynes & rsquo; misjudged caricature & mdash;that he had imposed a treaty of overwhelming harshness and severity. The French, however, have often maintained that that he was too lenient. David Watson considers the implications of Clemenceau & rsquo;s actions, his legacy, and what it subsequently entailed for the French.